TINJAUAN YURIDIS TERHADAP DISPENSASI NIKAH ANAK DI BAWAH UMUR (Analisis Putusan Nomor: 17/Pdt.P/2024/PA. Bji) - Silvyanas, Silvyanas; Fitrianto, Bambang; Sendy, Beby (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
Marriage dispensation is defined as an exemption from a duty or prohibition for men and women who have not met the requirements to marry, in the form of permission granted by the Religious Court to prospective brides who have not yet reached the age of 19 (nineteen) years and submit a dispensation request in accordance with Article 7, paragraph (2) of Law Number 16 of 2019. This research uses a normative juridical method, which means the research is based on an examination referring to and based on norms, legislation, legal theories and doctrines, court decisions, and other relevant literature related to the topic discussed in this research. The research was conducted using a qualitative method, specifically through data collection in the form of literature review. Factors contributing to early marriage include economic factors, premarital pregnancy, educational factors, parental factors, mass media and internet factors, family traditions, and cultural factors. In case number 17/Pdt.PA/2024/PA.Bjl, the judge decided to grant the request of Petitioner I and Petitioner II. This was based on evidence submitted to the Binjai Religious Court. One of the reasons for granting the dispensation was that Petitioner I and Petitioner II’s child had been living together like husband and wife and had been pregnant for three months. Both parents agreed and approved of the marriage. Marriage dispensation for minors is regulated in Article 7, paragraphs 1 and 2 of Law Number 16 of 2019. Dispensation, as referred to in Law Number 16 of 2019, means a deviation from the minimum marriage age limit set by the law, which is at least 19 (nineteen) years for both men and women.